The relationship between residents\' health and quality of neighborhood environment: a case study - Hamid Reza Azemati; Esmaeil Zarghami (Payesh, 2013)
Objective (s): Technological developments; economic trends and certain aesthetic perspective have caused less attention to the urban landscape; public open space and social relationships between citizens and their health. This study aimed to investigate about relationship between public open space and neighborhood environments and its impact on citizens’ health.Methods: This study has basically planned on focusing on the elements of urban open public spaces and its impact on the quality of relationships between citizens. Data were obtained from documents, studies, field observations, descriptions, photos and detailed maps of a given region in Tehran, Iran. After analysis and comparing health promotion measures and social interactions with mentioned issues the reasons were established.Results: Elements of the urban landscape that influence social norms and health of the citizens were identified.Conclusion: In designing the residential complexes, creation appropriate communication between green spaces and units can help to improve health and quality of life.